Delayed lower GI post polypectomy bleeding: nightmare of a surgeon- a case report - Mahmud, Mayin Uddin; Ahmed, Ershad Uddin; Mohsin, Mostafa Noor; Hossain, Motahhar (Journal of Surgical Sciences, 2021)
Introduction: Snare polypectomy is the gold standard treatment of colorectal polyp. Although colonoscopic polypectomy is generally safe, immediate or delayed post polypectomy bleeding may occur. The patient may present 1-30 days after successful polypectomy in delayed bleeding. Presentation of case: We present a case of delayed post polypectomy bleeding. The patient presented four days after snare polypectomy. The patient was hemodynamically unstable, and there was ongoing per rectal bleeding. The patient was initially resuscitated and colonoscopic measures were done to achieve hemostasis. Discussion: Delayed bleeding after polypectomy occurs in about 0.3-1.2% of all colonic polypectomies. Sloughing off of the scar and increasing the zone of necrosis are the primary pathogenesis of delayed bleeding. Polyp, patient and procedure-related factors are identified as responsible for delayed bleeding. Most patients are managed by only observation, but a few patients require repeat colonoscopy. Conclusion: Delayed post polypectomy bleeding is rare but lethal. Initial resuscitation and assessment of the patient is the key to managing such type of bleeding. Journal of Surgical Sciences (2021) Vol. 25(2) : 37-40